2019
DOI: 10.22190/fupes190303005b
|View full text |Cite
|
Sign up to set email alerts
|

eSPORTS AS A NEW PLAYGROUND

Abstract: With the emergence of digital media, traditional sport got computer platforms as a new kind of gaming space. eSports, as a modern form of gaming, has become an inevitable part of the digital game culture. The aim of this research is to determine if there is a connection between playing eSports video games and sport knowledge, competition skills, social interaction, skill building for problem solving and pleasurable stimulation which leads to emotional well-being. The survey encompassed 256 respondents who fill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…This can be fostered by attending live events or LAN-parties Jansz & Martens, 2005;Whalen, 2013), which also contribute to the findings that esport is a platform for socializing opportunities. This can occur in dedicated live events Jansz & Martens, 2005;McCauley et al, 2020;Whalen, 2013) or generally by engaging in the esport environment both online and offline (Baltezarević & Baltezarević, 2019;Fiskaali et al, 2020; Freeman & Wohn, Wohn & Freeman, 2020;Xiao, 2020). However, esport enthusiasts try to distinguish themselves based on the game they play (Karakus, 2015;, which results in tribal behavior among the different player bases (Hayday & Collison, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This can be fostered by attending live events or LAN-parties Jansz & Martens, 2005;Whalen, 2013), which also contribute to the findings that esport is a platform for socializing opportunities. This can occur in dedicated live events Jansz & Martens, 2005;McCauley et al, 2020;Whalen, 2013) or generally by engaging in the esport environment both online and offline (Baltezarević & Baltezarević, 2019;Fiskaali et al, 2020; Freeman & Wohn, Wohn & Freeman, 2020;Xiao, 2020). However, esport enthusiasts try to distinguish themselves based on the game they play (Karakus, 2015;, which results in tribal behavior among the different player bases (Hayday & Collison, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…(3) Ethics and fair play. Specific ethics, norms, and codices such as fair play, sportsmanship, and respect for the opponent are crucial elements of esport (Baltezarević & Baltezarević, 2019;Brown et al, 2018;Martončik, 2015;Seo, 2016), although they can occur in distinguished manner compared to traditional sport (Whalen, 2013). This also expresses itself through the fact that esport players see themselves as athletes (Schaeperkoetter et al, 2017).…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…eSport players need to have clear strategies and tactics in order to surpass their opponents (Hallmann & Giel 2018). Baltezarević and Baltezarević (2019) pointed out that eSport-based games can provide highly adaptable and motivating methods, and can help players develop the abilities of thinking and competitiveness, social interaction, as well as cultivating problem-solving skills. Seo (2013) also suggested that eSport helps players develop decision-making and problem-solving skills.…”
Section: Discussionmentioning
confidence: 99%
“…eSport is regarded as a new research field of sports management, education and practice (Funk, 2017;Funk et al, 2018), and is defined as a physical activity in which people use information and communication technology development to train their intellectual or physical abilities (Wagner, 2006;Wood et al, 2019). eSport is a kind of game associated with training sports knowledge, game skills, social interaction and problem-solving skills (Baltezarević & Baltezarević, 2019;Egliston, 2016;Kauweloa & Winter, 2019;Sousa et al, 2020). In addition, eSport also includes training, reflex, intelligence, teamwork and other elements (Arnaud, 2010).…”
Section: Introductionmentioning
confidence: 99%